Diversity and Distribution of the Inland Water Decapods of Sicily (Crustacea, Malacostraca) - Luca Vecchioni; Francesco Paolo Faraone; Fabio Stoch; Marco Arculeo; Federico Marrone (Diversity, 2022)
The current knowledge of Sicilian inland water decapod malacostracans is scarce and an updated synopsis on species distribution is lacking. Therefore, we reviewed the checklist and recent distribution of Sicilian inland water decapods based on published and unpublished records and novel observations with the aim of providing an exhaustive repository, also to be used as a sound baseline for future surveys. Overall, five native decapod species occur in the study area, i.e., the atyid shrimp Atyaephyra desmarestii, the palaemonid shrimps Palaemon adspersus, P. antennarius, and P. elegans, and the freshwater crab Potamon fluviatile, and their current local distributions are described. In addition, three alien species were recorded: the common yabby Cherax destructor and the red swamp crayfish Procambarus clarkii, strictly linked to inland waters, and the Atlantic blue crab Callinectes sapidus, a mainly marine species that can also colonise the lower stretches of rivers and coastal brackish waters. The collected data suggest the existence of a partial segregation of native versus non-native species, with the latter currently confined to coastal water bodies and the lower stretches of rivers. Moreover, the exclusively freshwater caridean A. desmarestii and P. antennarius show a parapatric distribution in the study area, which may suggest the existence of mutual exclusion phenomena. The results obtained raise some concerns about the effects of alien species on the native biota, and dedicated monitoring and management strategies should be implemented in order to better understand and mitigate their impact.